Pembiayaan Mudarabah di Pt. Bank Muamalat Indonesia Tbk. Cabang Pekanbaru Berdasarkan Hukum Islam - Hasan Basri (Perspektif Hukum, 2015)
The profit-sharing system has advantages with no causing the negative capital spread. The advantages of this system are the main reference for community of PT. Bank Muamalat Indonesia Tbk. (BMI) Branch Pekanbaru in developing the mudarabah financing. In the profit-sharing system, the ratio is determined at the time of making the contract based on the possibility of profit and loss. Data are collected by using interview to the informants in BMI. The collected data are analyzed in inductive method. The results show that the mudarabah financing in BMI Branch Pekanbaru does not fully apply the profit and loss sharing, but rather the revenue sharing. It means that the profit sharing is still based on the assumPT.ion of revenue. It can be illustrated that the bank can assume that someone can produce profits in a certain amount each month. This financing requires valuedly material and immaterial supports to anticipate moral hazard. The losses of mudarabah financing are fully borne by the owners of capital of BMI. Fund providers endure all the losses due to mudarabah. The losses of mudarabah financing are also charged to the customer due to customer negligence.